Antiviral Activity of Extracts from Basidiomycetes for Orthopoxviruses - T. V. Teplyakova (Проблемы особо опасных инфекций, 2012)
Carried out was evaluation of the effect of water extracts from basidiomycetes in Vero cell culture on variola virus, and vaccinia virus. Antiviral effect demonstrated Inonotus obliquus (Chaga), befungin and melanin from chaga, Ganoderma applanatum (Artist’s Bracket) , Fomitopsis officinalis (Larch Fungus) .